2019
DOI: 10.1177/0271121419832969
|View full text |Cite
|
Sign up to set email alerts
|

Participant Characteristics in Research on Interventions for Young Children With Challenging Behavior: A Systematic Review

Abstract: Intervention studies to reduce challenging behavior in young children below the age of 6 were reviewed for participant characteristics, including gender, race/ethnicity, disability, socioeconomic status, and language to evaluate the frequency of reporting and diversity of participant characteristics in this area of research. Interventions conducted in school, preschool, and home-based settings were included; 53 articles were reviewed. In these articles utilizing single case research or group designs ( n = 2,26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 91 publications
3
17
1
Order By: Relevance
“…Research and policy that adopts narrow conceptualizations of “readiness” can lead to interventions that blame families of Color as failing to support their children’s development (and themselves requiring intervention) while ignoring systemic educational and sociopolitical inequities (e.g., Baquedano-López et al, 2013; Dudley-Marling & Lucas, 2009). Similarly, the previously discussed behavioral intervention systematic review by Steed and Kranski (2020) found that multiple identity markers (e.g., race, gender, dis/ability, indicators of socioeconomic status) were rarely reported for individual participants, which limits the field’s understanding of how to address intersectional inequities related to behavioral expectations and exclusion. Thus, discourses and practices intended to support children’s development that only attend to dis/ability cannot necessarily support equity for multiply marginalized young children with dis/abilities.…”
Section: Using Discrit To Facilitate Justice-driven Inclusive Educatimentioning
confidence: 96%
See 4 more Smart Citations
“…Research and policy that adopts narrow conceptualizations of “readiness” can lead to interventions that blame families of Color as failing to support their children’s development (and themselves requiring intervention) while ignoring systemic educational and sociopolitical inequities (e.g., Baquedano-López et al, 2013; Dudley-Marling & Lucas, 2009). Similarly, the previously discussed behavioral intervention systematic review by Steed and Kranski (2020) found that multiple identity markers (e.g., race, gender, dis/ability, indicators of socioeconomic status) were rarely reported for individual participants, which limits the field’s understanding of how to address intersectional inequities related to behavioral expectations and exclusion. Thus, discourses and practices intended to support children’s development that only attend to dis/ability cannot necessarily support equity for multiply marginalized young children with dis/abilities.…”
Section: Using Discrit To Facilitate Justice-driven Inclusive Educatimentioning
confidence: 96%
“…Research can inadvertently minimize or obscure the effects of racism when race/ethnicity is not considered as an influence on the experiences of young children with dis/abilities and/or is simply reported as demographic information without consideration of its meaning. For example, multiple systematic reviews of early intervention and ECSE research have found that participants’ race/ethnicity is often not reported (e.g., Baril & Humphreys, 2017; Steed & Kranski, 2020). Steed and Kranski (2020) found that race/ethnicity was reported in less than half of studies examining interventions to address young children’s perceived challenging behavior.…”
Section: Using Discrit To Facilitate Justice-driven Inclusive Educatimentioning
confidence: 99%
See 3 more Smart Citations